(untitled) (Annals of Medical Research, 2021)
Aim: Peak or onset latency difference of the median and ulnar nerves can be used in the median-versus-ulnar digit 4 sensory comparison study (MUD4CS) for electrodiagnosis of carpal tunnel syndrome (CTS). This study aimed to investigate the differences in results while using peak or onset latency difference.Material and Methods: The hands of patients with clinical CTS diagnosis but normal median nerve conduction study (NCS) results were included retrospectively in this study. NCSs of the median and ulnar nerves with onset and peak latencies in MUD4CS were recorded. Onset and peak latency differences of the two nerves and also peak-onset latency difference of the median nerve in MUD4CS were calculated. The hands were divided into two groups according to MUD4CS findings: abnormal and normal. The hands in the abnormal group were also divided into peak and onset subgroups.Results: A total of 277 hands were included in this study. Abnormal MUD4CS results were observed in 103 hands; 77 hands based on onset latency difference, and in 76 hands based on peak latency difference. Median sensory conduction velocity was slower and amplitude was smaller in the abnormal group than in the normal group (p=0.003, p=0.027 respectively). Median peak-onset latency difference was significantly greater in the peak subgroup than in the onset subgroup (p=0.0001).Conclusion: It may be more useful to measure both peak and onset latency differences when diagnosing CTS because some cases may be overlooked by using a single latency difference.